DIMENSI SALURAN PRIMER PADA DAERAH IRIGASI WERA KECAMATAN DOLO BARAT KABUPATEN SIGI (Overview of Dimensions Line Primer on Irrigation Area Wera District of West Dolo Sigi) - Sulfiati Sulfiati (Siimo Engineering, 2017)
The review of the primary channels on irrigated area Wera is one of the efforts to improve the optimization function of irrigation networks, considering the age of the channel that is long enough and the circumstances climate of uncertainty so that it can be easily damaged, which is one of the causes is the scouring continually on the channel walls and excessive sediment so that the flow of water in the channel is not optimal in serving the irrigated plots. In this review used data collection methods, both primary and secondary, primary data by direct observation in the field and secondary data by collecting data from relevant agencies trustworthy validity. then the data is processed and analyzed to produce a theoretical data, namely: the value of discharge (Q) = 0.466 m ^ 3 / s, the channel base width (b) = 0.85 m, height of primary air duct  (h) = 0, 72 m. by the calculation of the channel bottom slope (I) = 0.00019. While the dimensions of the existing primary channel, the channel base width (b) = 0.80 m and height of water (h) = 0.80 m, with the same discharge value.Keywords : Primary Channels and Secondary Channels, Existing Primary Channel and Existing Secondary Channel, Irrigated Area